Pengaruh Emosi Positif Dan Stimuli Lingkungan Terhadap Kecendrungan Shopaholic (Studi Fakultas Ekonomi Bisnis Universitas Harapan Medan) - Popo Nasution, Martua Amai (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2024)
This study aims to determine the effect of positive emotions on shopaholic tendencies and environmental stimuli on shopaholic tendencies partially. To determine the effect of positive emotions and environmental stimuli on shopaholic tendencies. The population in this study was 374 and using the Arikunto formula of 30% obtained a sample of 112. The analysis technique used was multiple linear regression. The results showed that positive emotions had a positive and significant effect on shopaholic tendencies, environmental stimuli had a positive and significant effect on shopaholic tendencies, positive emotions and environmental stimuli had a positive and significant effect on shopaholic tendencies.